Representasi Gender dan Budaya dalam Buku Ajar Bahasa Indonesia untuk Siswa Kelas VIII Tingkat Sekolah Menengah Pertama - Jamila Tun Nabilah Hasanuddin; Marwiah Marwiah; Aco K (Universitas Palan, 2026)
This research aims to analyze how gender and culture are represented in the Grade VIII Indonesian language textbook of the Merdeka Curriculum. The focus is on various aspects of gender representation, such as the depiction of characters, their roles, activities, attributes, social status, gender equality, and stereotypes related to gender. Additionally, the study explores cultural representation, which encompasses cultural forms, diversity, local traditions, context, ways of presentation, and the cultural values expressed in the textbook's texts and illustrations. The methodology employed is descriptive qualitative research with a content analysis framework. Data were gathered through documenting and note-taking methods on the content of the textbook, followed by an analysis process that includes identification, classification, interpretation, and drawing conclusions. Findings indicate that the gender representation in the textbook predominantly portrays men as leading figures in public roles, leadership, and decision-making, whereas women are mainly shown in nurturing, domestic, and supportive capacities. On the other hand, the cultural representation illustrates the variety of Indonesian culture by showcasing regional customs, languages, art forms, traditional cuisine, practices, and societal norms. The study concludes that although the textbook presents cultural diversity adequately, there is a need for improvement in gender representation balance to better reflect equality values in the educational experience.